2011
DOI: 10.1016/j.molcata.2010.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of cyclooctene and cyclohexene with hydrogen peroxide catalyzed by bis[3,5-bis(trifluoromethyl)-diphenyl] diselenide: Recyclable catalyst-containing phases through the use of glycerol-derived solvents

Abstract: A green strategy has been explored for olefin epoxidation which combines renewable solvents (derived from glycerol), aqueous hydrogen peroxide, and catalyst recycling (a seleninic acid derivative). The use of fluorinated glycerol derivatives allows good catalytic activity in the epoxidation of cyclooctene and cyclohexene with aqueous hydrogen peroxide, preventing epoxide hydrolysis to a great extent, which is particularly remarkable in the case of cyclohexene. Furthermore, recycling of the catalytically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Fluorinated glycerol derivatives exhibited good catalytic activity in the epoxidation of cyclooctene and cyclohexene with hydrogen peroxide in an aqueous system and prevented epoxide hydrolysis to a great extent, particularly in the case of cyclohexene, as described by the same authors (García-Marín et al, 2011).…”
Section: Glycerol Derivativessupporting
confidence: 55%
“…Fluorinated glycerol derivatives exhibited good catalytic activity in the epoxidation of cyclooctene and cyclohexene with hydrogen peroxide in an aqueous system and prevented epoxide hydrolysis to a great extent, particularly in the case of cyclohexene, as described by the same authors (García-Marín et al, 2011).…”
Section: Glycerol Derivativessupporting
confidence: 55%
“…The high performance of [F, 0, F] in the transglycosylation reaction was realized by Bayon et al 43 and Sandoval et al 44 with significant improvement on the selectivity and yield over traditional organic solvents. Aldea et al 45 observed better results in the Kharasch-Sosnovsky allylic oxidation of cycloalkenes, and Garcia-Marin et al 46 obtained similar results in the epoxidation of cyclooctene in [F, 0, F]. Aldea et al 47 reported high yield of enantioselective conjugate reduction of ethyl (E)-3-phenylbut-2-enoate in [F, 0, F].…”
Section: Evaluating the Green Metrics Of Tfge Synthesismentioning
confidence: 97%
“…Thus, fluorinated glycerol derivatives, such as the closely related 1,3-bis(2,2,2trifluoroethoxy)propan-2-ol [3F.0.3F], have been successfully used as reaction media in epoxidation and enzymatic reactions. 38,[47][48][49]…”
Section: Scope Of the Synthesis With Different Bases And Alcoholsmentioning
confidence: 99%
“…Some of them, like the fluoroalkyl glycerol ethers, have special properties that made them suitable for the substitution of ionic liquids in some catalytic applications. [36][37][38] Another key point is the toxicological profile of these compounds, an aspect that is currently under study in our group. 39,40 Last, but not least, the synthetic procedures to obtain this family of glycerol derivatives should meet as much as possible the principles of Green Chemistry and, in order to be of practical applicability, they should also meet economic criteria.…”
Section: Introductionmentioning
confidence: 99%